Postural Analysis Methods in Orthodontic Patients: A Review - Bertash М. А.; Drohomyretska М. С. (Actual Dentistry, 2026)
In recent decades, increasing attention has been paid to the potential influence of masticatory system disorders, such as malocclusion, on whole-body posture. The number of patients seeking simultaneous treatment for dental anomalies and postural disorders continues to rise. This review aims to analyze research methods used to assess posture in relation to the stomatognathic system. The anatomical and functional interconnection between the masticatory apparatus and postural regulation has led to several hypotheses regarding the correlation between occlusal and postural disorders. These ideas have gained wide public resonance, partly due to their dissemination in the media. Evidence supports the role of the dento-maxillary system—particularly occlusion and the temporomandibular joint—in maintaining vertical postural stability. Furthermore, the relationship between spinal alignment, head position, and occlusion underscores the importance of a comprehensive approach to diagnosing and managing occlusal disorders and temporomandibular joint pathology. Purpose. To identify, based on published literature, the principal methods of postural analysis and evaluate their applicability in patients with occlusal pathology. Materials and Methods. A bibliosemantic approach was employed, involving a targeted search of scientific publications in the PubMed database and the multidisciplinary journal Scientific Reports. Results. The review expands current knowledge of methods for assessing the maxillofacial region and postural balance. It highlights advances in diagnostic techniques, the integration of modern technologies, and the value of interdisciplinary collaboration in optimizing postural balance in orthodontic patients. Conclusions. The adaptive properties of the organism with respect to posture and the stomatognathic system demonstrate a significant connection between the cranio-cervical complex and overall postural regulation. Physiological occlusal relationships and harmonious occlusion exert a notable influence on postural balance. Recognizing this interrelationship facilitates accurate diagnosis and supports the development of innovative diagnostic and therapeutic approaches for orthodontic patients with postural disorders associated with stomatognathic pathology.